Evaluation of Financial Support Workshops for Patients Under State Pension Age With Degenerative Cervical Myelopathy: Survey Study - Tanzil Rujeedawa; Zahabiya Karimi; Helen Wood; Irina Sangeorzan; Roy Smith; Iwan Sadler; Esther Martin-Moore; Adrian Gardner; Andreas K Demetriades; Rohitashwa Sinha; Gordan Grahovac; Antony Bateman; et al. (JMIR Formative Research)
Abstract BackgroundDegenerative cervical myelopathy (DCM), a form of slow-motion and progressive spinal cord injury caused by spinal cord compression secondary to degenerative pathology, leads to high levels of disability and dependence, and may reduce quality of life. Myelopathy.org is the first global scientific and clinical charity for DCM, providing an accessible platform freely disseminating information relevant to the DCM diagnosis and its treatment. Significant transient and long-term change to earnings do occur and can thrust individuals into poverty. People with DCM face many challenges accessing state financial assistance. This can have a cumulative negative financial effect due to the association between DCM and low socioeconomic index. Financial support available to patients under pension age include Universal Credit (UC), a payment that helps with living costs, and Personal Independence Payment (PIP), which helps with extra living costs if someone has both a long-term health condition or disability and difficulty doing certain everyday tasks. ObjectiveThis study aimed to assess if delivering workshops centered around access to financial support could assist people with DCM living in the United Kingdom. MethodsA series of 2 internet-based workshops was targeted at accessing financial support for English patients under the state pension age, with an anonymized survey delivered to participants after each session. The first session was on UC and the second on PIP. The survey consisted of a mixture of Likert scales, free text and yes or no answers. Survey responses were analyzed using descriptive statistics and free text answers underwent inductive thematic analysis. ResultsThe average rating on the use of UC was 9.00/10. Presession self-rated confidence levels were 5.11/10 rising to 8.00/10. The mean score of wanting further similar sessions was 8.67/10 with 56% (5/9) of participants wanting one-to-one sessions. For PIP, the average session use rating was 10/10. Presession self-rated confidence levels were 4.43/10 rising to 9.57/10. The mean score of wanting further similar sessions was 8.71/10, with 43% (3/7) of participants wanting one-to-one sessions . Following inductive thematic analysis, themes regarding the usefulness of such sessions and the challenges to accessing financial support emerged. One participant gave negative feedback, which included the length of the session and perceived problems around confidentiality and data protection. ConclusionsThe pilot series was largely perceived as a success, with participants finding them useful and increasing their self-rated confidence in navigating the UK financial support system. Given the small sample size, it is hard to predict the success of future sessions. Finally, given that the hurdles in accessing financial support extend beyond DCM, such workshops may be relevant to other organizations.